MODEL KOLABORASI PEMASARAN ONLINE UNTUK MENINGKATKAN DAYA SAING USAHA MIKRO DALAM MENGHADAPI ERA DIGITAL DI KOTA SURABAYA - Endang Siswati (Fakultas Ekonomi Universitas PGRI Adi Buana, 2021)
The approach used in this research is qualitative, to find an overview of how micro businesses find solutions in dealing with the digital era, this research is located in Surabaya. After the data obtained from observations and interviews were collected, then data triangulation was carried out, method and theory triangulation was then analyzed. The results of the study illustrate that the management of micro-enterprises is currently faced with the digital world, some of which are not ready to enter online-based businesses. Micro-enterprises are deemed necessary to seek breakthroughs in order to be able to run their business online while still managing them offline. From several alternatives, an online marketing collaboration model can be chosen with creative groups who understand digital, this is a solution for micro businesses that are not ready to enter online business, to increase sales. This is corroborated by research by AA Anggraeni (2008), facing the explosion in the use of online marketing, small business actors must be prepared to run an online business. In line with Wirapraja, A., & Aribowo, H. (2018) the existence of globalization is now inevitably market players must review their marketing programs in order to continue to exist in the competition.